Response of the atmospheric convective boundary layer to surface inhomogeneities - Hadfield, Mark Gregory, author (Colorado State University. Libraries, 1988)
Large-eddy simulations (LES) of the atmospheric convective boundary layer have been conducted with a surface sensible heat flux that either is constant or varies on a spatial scale comparable to the boundary layer depth. The horizontally homogeneous simulations have been compared with previous LES, laboratory and atmospheric studies. The dynamics of the simulated turbulence and the model's sensitivity to the subgrid diffusivity have been investigated. In general, the present model gives results similar to previous large-eddy simulations. All the LES models simulate a field of convective eddies having approximately the correct velocity and spatial scales, and with the crucial property that kinetic energy is transported vigorously upwards through the middle levels. Several failings of the models have been identified, including a tendency to underpredict temperature variance and to overpredict vertical velocity skewness in the upper boundary layer. The surface heat-flux variations are one-dimensional and sinusoidal with a wavelength between one and four times the boundary layer depth. Simulations have been carried out with zero wind or with a light mean wind perpendicular to the perturbations. Several effects have been identified, though some are evident only after a great deal of averaging. They include mean circulations in phase with the surface perturbations, modulation of the turbulence throughout the boundary layer and modifications (usually slight) to the profiles of horizontally averaged statistics. The mean boundary layer depth remains horizontally uniform. Most of the effects increase as the wavelength of the surface perturbation is increased and decrease with an imposed mean wind. The processes maintaining the mean temperature field and the mean circulation have been analyzed. A time scale for kinetic energy transfer from the circulation to the turbulence has been defined and found to be surprisingly short in some cases. The turbulent stress budgets have also been examined: the effects of turbulent buoyancy fluctuations and of interactions between the circulation and the turbulence have been distinguished. Elevated-plume dispersion has been studied using a Lagrangian particle model. Circulations driven by the surface heat-flux perturbations affect the ground level concentration.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1988.
Keywords: Turbulent boundary layer